Relationships between sleep, athletic and match performance, training load, and injuries: a systematic review of soccer players - Clemente, Filipe Manuel (2021)
The purpose of this systematic review was to summarize available evidence regarding the relationships between sleep and (i) athletic and match performance, (ii) training load, and (iii) injuries in soccer players. A systematic review of EBSCOhost (SPORTDiscus), PubMed, Cochrane Library, FECYT (Web of Sciences, CCC, DIIDW, KJD, MEDLINE, RSCI, and SCIELO) databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 297 titles were identified, of which 32 met the eligibility criteria. Results revealed that soccer players are no exception for sleep inadequacy. Although there was inconsistency in the findings, some studies suggested that sleep restrictions in soccer negatively affected athletic and match performance while also increasing the number and severity of musculoskeletal injuries. On the other hand, inconsistent results were found between sleep and athletic and match performance, and training load in soccer players. Physiological responses (and their intensity) during drill-based games were not influenced by changes in sleep. The available evidence is inconsistent; however, it appears to suggest that poor sleep affects soccer players' performance and increases the risk of injury. However, it remains important to study this complex relationship further.